Renewable Energy Consumption and Green Growth in Sub-Saharan Africa - Brian Tavonga Mazorodze (Energies)
The debate on renewable energy consumption and green growth is yet to be empirically settled. Motivated by the dearth of literature in sub-Saharan Africa on this subject, this study examines the impact of renewable energy consumption on green growth using a panel of 22 sub-Saharan countries observed between 1990 and 2019. It criticizes the existing literature for inadequately addressing cross-sectional dependence and inappropriately assuming homogeneity in the way renewable energy consumption affects green growth across countries. A comparison of the commonly applied estimator in the literature which ignores the above two violations, and the preferred estimator suggests that the current state of knowledge could be fundamentally flawed. While the estimator commonly applied in the literature replicates the largely reported positive and direct impact of renewable energy on green growth, the preferred estimator finds the impact insignificant. It instead finds that green growth is primarily driven by gross capital formation, rather than renewable energy consumption. This study additionally examines the effect of renewable energy on several types of environmental damage. Renewable energy is found to significantly reduce CO2 emissions only. The conclusion is therefore that renewable energy does not have a direct impact on green growth, although it helps reduce CO2 emissions.